Professionalism and governance - Quddus, S. M. Abdul (Netinseach International, University of Dhaka, Bangladesh, 2015)
As a result of globalization, there are amazing developments and transformation of government and administration systems around the globe. Globalization accelerate structural reforms of the public sector governance through “marketization” of public service delivery to citizens and establish a system of global corporate dependency through “agencification” of national economies that are led by advocates of the ideology, which ensures that some kinds of international “standards” are in place for state policies to follow. The doctrine of “standards” which refers to relentless competition in the pursuit of profit, and individual satisfaction or value for money and the definition of goals and targets, indicators of outputs, and success in both quantitative and qualitative terms for professional services (Carter, 1989; Day & Klein, 1987; Shore & Wright, 2000). This paper focuses on the problems, perspectives and solutions related to professionalism i.e. result and quality oriented public sector governance. Our specific questions are: a) what are the meaning and scenario of professionalism in public administration in the West as well as in the Eastern perspectives? b) What are the theoretical underpinnings of professionalism and governance from the Western and the Eastern perspectives? and c) How to deal with problems of professionalism in governance? This paper argues for studying professionalism from both the Western and the Eastern perspectives in order to find a holistic solution of the problem.